2021
DOI: 10.3389/fgene.2021.701658
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Genes Affecting Rice Grain Zinc Content Through Candidate Gene-Based Association Analysis

Abstract: Several key genes governing Zn homeostasis and grain zinc content (GZC) have been functionally characterized. However, the effects of these genes in diverse breeding populations have not been evaluated; thus, their availability in breeding is unclear. In this study, the effects of 65 genes related to rice zinc responses on GZC were evaluated using two panels of breeding lines, and the superior haplotypes were identified. One panel consisted of mega varieties from the International Rice Research Institute (IRRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The essential component includes identification of the target population and staple food (crop) consumption, establishing a breeding baseline and nutrient target levels, and screening and characterizing germplasm for target nutrients. The outcomes of the discovery phase will guide the Dwivedi et al 10.3389/fpls.2023.1119148 Frontiers in Plant Science frontiersin.org Rice qGZn9a linked with high-grain Zn levels in O. meridionalis W1627 but with reduced fertility levels; a partial defect in anther dehiscence correlates with increased grain Zn; eight candidate genes in the qGZn9a region, with one specifically expressed in the developing anther and possibly regulates anther dehiscence; thereby, a balancing selection is needed to effect simultaneous improvement Ogasawara et al, 2021 Two QTL qZPR.1.1 and QTL qZPR.11.1 on chromosome 1 and a common QTL on chromosome 2 for grain Zn in polished rice; two candidate genes related to transporters Suman et al, 2021 Haplotype-based association mapping involving 65 genes related to Zn responses on three diverse panels revealed five (OsNRAMP6, OsYSL15, OsIRT1, OsIDEF1, and OsZIFL7; PVE 7.70%-15.39%), three (OsFRDL1, OsIRT1, and OsZIP7, 11.87%-17.99%), and two (OsYSL7 and OsZIP7, 9.85%-10.57%) genes, respectively, associated with grain Zn in diversity panels from Southeast Asia (SEA) and South China (SC), and MAGIC population; haplotype analysis revealed that Hap1-OsNRAMP5, Hap5-OsZIP4, Hap1-OsIRT1, Hap3-OsNRAMP6, Hap6-OsMTP1, and Hap6-OsYSL15 had the largest effects for Zn in SEA and Hap3-OsOPT7, Hap4-OsIRT2, Hap4-OsZIP7, Hap5-OsIRT1, and Hap5-OsSAMS1 had the most significant effects in the SC panels Liu et al, 2021a Zn in polished grains associated with SNPs located in three putative candidate genes on chromosomes 3 and 7; chromosome 7 genomic region colocalized with previously identified genomic regions (rMQTL 7 . 1 ) and OsNAS3 candidate gene Babu et al, 2020 Six, 7, 11, and…”
Section: Cross Breeding and Genomic-assisted Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential component includes identification of the target population and staple food (crop) consumption, establishing a breeding baseline and nutrient target levels, and screening and characterizing germplasm for target nutrients. The outcomes of the discovery phase will guide the Dwivedi et al 10.3389/fpls.2023.1119148 Frontiers in Plant Science frontiersin.org Rice qGZn9a linked with high-grain Zn levels in O. meridionalis W1627 but with reduced fertility levels; a partial defect in anther dehiscence correlates with increased grain Zn; eight candidate genes in the qGZn9a region, with one specifically expressed in the developing anther and possibly regulates anther dehiscence; thereby, a balancing selection is needed to effect simultaneous improvement Ogasawara et al, 2021 Two QTL qZPR.1.1 and QTL qZPR.11.1 on chromosome 1 and a common QTL on chromosome 2 for grain Zn in polished rice; two candidate genes related to transporters Suman et al, 2021 Haplotype-based association mapping involving 65 genes related to Zn responses on three diverse panels revealed five (OsNRAMP6, OsYSL15, OsIRT1, OsIDEF1, and OsZIFL7; PVE 7.70%-15.39%), three (OsFRDL1, OsIRT1, and OsZIP7, 11.87%-17.99%), and two (OsYSL7 and OsZIP7, 9.85%-10.57%) genes, respectively, associated with grain Zn in diversity panels from Southeast Asia (SEA) and South China (SC), and MAGIC population; haplotype analysis revealed that Hap1-OsNRAMP5, Hap5-OsZIP4, Hap1-OsIRT1, Hap3-OsNRAMP6, Hap6-OsMTP1, and Hap6-OsYSL15 had the largest effects for Zn in SEA and Hap3-OsOPT7, Hap4-OsIRT2, Hap4-OsZIP7, Hap5-OsIRT1, and Hap5-OsSAMS1 had the most significant effects in the SC panels Liu et al, 2021a Zn in polished grains associated with SNPs located in three putative candidate genes on chromosomes 3 and 7; chromosome 7 genomic region colocalized with previously identified genomic regions (rMQTL 7 . 1 ) and OsNAS3 candidate gene Babu et al, 2020 Six, 7, 11, and…”
Section: Cross Breeding and Genomic-assisted Breedingmentioning
confidence: 99%
“…qGZn9a linked to high-grain Zn in Oryza meridionalis also adversely affects fertility levels. One of the eight candidate genes in qGZn9a specifically expressed in the developing anther and possibly regulated anther dehiscence, which suggests that a balancing selection is needed to ensure simultaneous improvement in rice ( Ogasawara et al., 2021 ), while haplotype-based association mapping involving 65 genes related to Zn responses on diverse germplasm panels and MAGIC populations revealed diversity panel- or population- specific candidate genes associated with high seed Zn content ( Liu et al., 2021a ). Many of the candidate genes associated with Fe and Zn uptake, transport, storage, and regulation in wheat were orthologs of known Arabidopsis and rice genes related to Fe and Zn homeostasis ( Tong et al., 2022 ), while SNPs mapped on chromosome 1A and 2A in wheat genome significantly associated with seed Fe and Zn content had no adverse effects on seed weight ( Liu et al., 2021b ).…”
Section: Spatial and Temporal Distribution And Accumulation Of Fe And Znmentioning
confidence: 99%
“…Identifying minor genes of complex traits by CAS were conducted in Arabidopsis , rice, maize and common wheat ( Zhao et al., 2015 ). Haplotype is the combination of alleles at different position on the same genomic regions for common inheritance ( Liu et al., 2021 ), effective than SNP (Single nucleotide polymorphism) and InDel (Insertion-deletion) in crop marker-assisted selection (MAS) breeding ( Li et al., 2017 ; Resende et al., 2017 ; Prodhomme et al., 2020 ). Superior haplotype identification has been proven to be an effective way to identify genes associated with complex traits and availability for crop breeding ( Bevan et al., 2017 ; Abbai et al., 2019 ; Sinha et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on genome-wide association studies, 11 genes were selected for haplo-pheno analysis to identify the superior haplotypes for resistant starch, the glycemic index and grain and cooking quality in rice [21]. Liu et al [22] evaluated the effects of 65 genes related to rice zinc responses on grain zinc content using two panels of breeding lines, and superior haplotypes were identified. Abbai et al [23] conducted a candidate gene-based association study for 120 genes and identified 21 strongly associated genes governing 10-grain yield and quality traits and identified superior haplotypes for the associated genes upon phenotyping the subset of the 3k rice genome panel.…”
Section: Introductionmentioning
confidence: 99%